The contribution of the supraspinatus muscle at sub-maximal contractions. (8th February 2018) - Phillips, David; Kosek, Peter; Karduna, Andrew
Abstract: During maximum effort, the supraspinatus muscle contributes approximately 50% of the torque need to elevate the arm, but this has not been examined at sub-maximal levels. The purpose of this study was to determine the contribution of the supraspinatus muscle to shoulder elevation at sub-maximal levels. Seven healthy subjects (four males, three females) performed isometric ramp contractions at the shoulder. Middle deltoid electromyography (EMG) and force applied at the wrist were collected before and after a suprascapular nerve block. For the same level of deltoid EMG, less external force will be measured after the nerve block as the supraspinatus muscle no longer contributes. The difference between the EMG/force curve was the contribution of the supraspinatus muscle. The supraspinatus contributed 40%, 95% CI [32%–48%], to shoulder elevation. The effect of angle ( p = .67) and % maximal voluntary contraction ( p = .13) on supraspinatus contribution were not significant. The maximum is slightly less than reported in a previous suprascapular nerve block study using maximal contractions. The results from this study can be used to assess supraspinatus contribution in rotator cuff tears, after rehabilitation interventions, and as a restraint in computation modelling.